1993
DOI: 10.1007/bf00210955
|View full text |Cite
|
Sign up to set email alerts
|

Poor plasma status of carotene and vitamin C is associated with higher mortality from ischemic heart disease and stroke Basel Prospective Study

Abstract: Previous cross-cultural comparisons of the mortality from ischemic heart disease in European communities with associated plasma levels of essential antioxidants have revealed strong inverse correlations for vitamin E and relatively weak correlations for other antioxidants. Similarly, in a case-control study in Edinburgh low plasma levels of vitamin E were significantly associated with an increased risk of previously undiagnosed angina pectoris whereas low levels of other essential antioxidants lacked statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
1
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(123 citation statements)
references
References 12 publications
6
113
1
3
Order By: Relevance
“…This contrasts with results in healthy middle-aged US smokers [14], and in Swiss with a 42% smoking prevalence [15]. Since smoking was strongly predictive in PRIME and was associated with low carotenoid levels, these results [14,15] may have been due to confounding by lifestyle factors, e.g. fruit/vegetable intake.…”
Section: Carotenoidscontrasting
confidence: 69%
“…This contrasts with results in healthy middle-aged US smokers [14], and in Swiss with a 42% smoking prevalence [15]. Since smoking was strongly predictive in PRIME and was associated with low carotenoid levels, these results [14,15] may have been due to confounding by lifestyle factors, e.g. fruit/vegetable intake.…”
Section: Carotenoidscontrasting
confidence: 69%
“…There have been three major epidemiological complementary studies of the association between low plasma concentration of diet-derived antioxidants and the risk of IHD and stroke: the WHO MONICA Project (1989); the Edinburgh Angina-Control Study (Riemersma et al 1991); the Basel Prospective Study (Gey et al 1993). These studies consistently revealed an association between increased risk of IHD (and stroke) and low plasma concentrations of antioxidants.…”
Section: Fruit and Vegetables (Antioxidants)mentioning
confidence: 99%
“…Antioxidants prevent the oxidation of low-density lipoproteins and may therefore reduce the occurrence of ischaemic heart disease and cerebrovascular disease (CVA) (Steinberg et al, 1989;Gey et al, 1993). Since¯avonoids are effective antioxidants, it is plausible that they provide protection against CVA (Shutenko et al, 1999).…”
Section: Introductionmentioning
confidence: 99%